Small-Scale Telomere Repeat Sequence Content Assay Using Pyrophosphorolysis Coupled with ATP Detection. (December 2002) - Learish, Randall D.; Shultz, John; Ho, Samuel; Bulleit, Robert F.
Studies of telomere length have been carried out in diverse areas of research. However, current methods to measure telomeres are cumbersome and not amenable to high-throughput analyses. Using a coupled pyrophosphorolysis/trans-phosphorylation reaction, we have developed a novel assay to quantitate telomere sequence content in a single tube or 96-well format. The method uses a telomere-specific oligonucleotide probe to sample nanogram quantities of DNA without PCR amplification. Polymerase and kinase enzymes drive the production of ATP, which is then monitored with a luciferase enzyme reporter system. Using this approach, we demonstrated that the luminescent output was linear across a 100-fold range of DNA input, and the assay was sensitive to 0.4–1 ng DNA. A control probe reaction and a DNA quantitation reaction were also designed using the same pyrophosphorolysis technology to correct for background activity and normalize the signal against variations in DNA input, respectively. Finally, we show that the normalized luminescent signal generated by this new method is highly correlated to the telomere restriction fragment length for six human cell lines.